Human rights in the civil-military ditadura popular cancer in the 1960’s and 1970’s (Research, Society and Development, 2020)
The present work presents the experience obtained by teachers during the execution of the teaching project Cultural production in the 1960s and 1970s: modern Brazil in MPB songs developed at the Federal Institute of Alagoas, Marechal Deodoro campus. Through the discussion of the work of artists identified with the MPB we try to understand the country in the period of the Civil-Military Dictatorship. Our proposal was to develop history teaching practices that took into account aspects related to human rights and cultural production in the 1960s and 1970s. In this way, we intend to know and reinterpret with our students the history of Brazil by the bias of selected songs by Chico Buarque, Caetano Veloso, Belchior, Gonzaguinha, Tom Zé, Elis Regina, Wilson Simonal, Odair José and others. Topics such as urban, social and generational transformations that occurred at that moment from the prism of these artists were approached. Our methodology consisted of oral exhibitions with the use of media resources (sound and video) and dialogued class. The participation and interaction of the students were fundamental in our proposal in the activities developed during the execution of the project, giving it an action research character. Finally, our intention was to offer a tool for discussion and reinterpretation of human rights in the history of Brazil with a more attractive, critical and interactive approach.